The Dividend-Price Ratio and Expectations of Future Dividends and Discount Factors - Campbell, John Y.; Shiller, Robert J. (Review of Financial Studies, 1988)
[A dividend-ratio model is introduced here that makes the log of the dividend-price ratio on a stock linear in optimally forecast future one-period real discount rates and future one-period growth rates of real dividends. If ex post discount rates are observable, this model can be tested by using vector autoregressive methods. Four versions of the linearized model, differing in the measure of discount rates, are tested for U.S. time series 1871-1986 and 1926-1986: a version that imposes constant real discount rates, and versions that measure discount rates from real interest rate data, aggregate real consumption data, and return variance data. The results yield a metric to judge the relative importance of real dividend growth, measured real discount rates, and unexplained factors in determining the dividend-price ratio.]